Heavy Metal (Pb, Hg) Contained in Blue Swimming Crab (Portunus pelagicus Linnaeus, 1758) in Cengkok Coastal Waters, Banten Bay, Indonesia - Nadya Febrianessa; Sulistiono Sulistiono; Agustinus Mangaratua Samosir; Masashi Yokota (Marine Science Department Diponegoro University, 2020)
Increasing number of industries and settlements in Banten Bay were subsequently followed by an increase in the amount of waste, whether in the form of solid, liquid or gas that can pollute the environment. One of the toxic pollutants is heavy metal.The entry mechanism of the heavy metal Mercury (Hg) and Lead (Pb) in body of the crab (Portunus pelagicus), namely through the process of digestion food. This study was conducted for 6 months, from March to August 2019, and aimed to analyze the heavy metal content levels (Pb and Hg) and the safe consumption level of the blue swimming crab (Portunus pelagicus) in the waters. The heavy metal concentration in the meat was measured through the AAS (Atomic Absorption Spectrophotometer) AA 7000 series Shimadzu. The analysis showed that the Pb and Hg contained in the blue swimming crab were still under the quality standards. Also, the bio-concentration factors of the blue swimming crab were low (<100). Water quality data observed as temperature, salinity, TSS, pH, dissolved oxygen, turbidity, and transparency stayed in the range of tolerable limits for the survival of marine organisms. Maximum weekly intake calculation refers to the tolerable limits issued by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). The JECFA recommends calculating the PTWI of each heavy metal if it accumulates in the human body for methyl mercury 1.6 μg.kg bw.week-1 and for lead not exceed 25 μg.kg bw.week-1. The safety consumption level of blue swimming crab from Cengkok Coastal water was 2.3 kg of meat.week-1 (for adults) and 0.6 kg of meat.week-1 (for children).